Mechanical and metabolic power in accelerated running-Part II: team sports - Osgnach, C.; di Prampero, P. E.; Zamparo, P.; Morin, J. B.; Pavei, G. (European Journal of Applied Physiology, 2024)
Purpose This manuscript is devoted to discuss the interplay between velocity and acceleration in setting metabolic and mechanical power in team sports.